Phép tách suy biến của một quan hệ trong cơ sở dữ liệu - Vuong, Le Tien (Journal of Computer Science and Cybernetics, 2018)
In this paper we introduced the notion of ternary degenerate decomposition of a relation and inverstigated its properties. By application of this degenerate decomposition it can be captured more semantics of data in a relational database.